2020
DOI: 10.1002/1878-0261.12676
|View full text |Cite
|
Sign up to set email alerts
|

LNCAROD is stabilized by m6A methylation and promotes cancer progression via forming a ternary complex with HSPA1A and YBX1 in head and neck squamous cell carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) constitute approximately 4% of all cancers worldwide. In this study, we analyzed the expression profile of the long noncoding RNA (lncRNA) of 502 HNSCC patients from The Cancer Genome Atlas database. Among the differentially expressed lncRNAs between HNSCC and normal samples, LNCAROD is overexpressed in HNSCC and associated with advanced T stage and shortened overall survival. The N6-methyladenosine (m6A) modification mediated by METTL3 and METTL14 enhanced the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(133 citation statements)
references
References 41 publications
2
123
0
Order By: Relevance
“…Long non-coding RNA 00958 (LINC00958) is upregulated by METTL3 and facilitates HCC cell migration and invasion by sponging miR-3619-5p [65]. METTL3/14 enhance the migration of head and neck squamous cell carcinoma (HNSCC) by upregulating lncRNA activating regulator of DKK1 (LNCAROD) [66]. METTL3-family with sequence similarity 225 member A (FAM225A)-integrin β3 (ITGB3)-FAK/PI3K/Akt axis facilitates the metastasis of nasopharyngeal cancer [67].…”
Section: Tumor Invasion and Metastasismentioning
confidence: 99%
“…Long non-coding RNA 00958 (LINC00958) is upregulated by METTL3 and facilitates HCC cell migration and invasion by sponging miR-3619-5p [65]. METTL3/14 enhance the migration of head and neck squamous cell carcinoma (HNSCC) by upregulating lncRNA activating regulator of DKK1 (LNCAROD) [66]. METTL3-family with sequence similarity 225 member A (FAM225A)-integrin β3 (ITGB3)-FAK/PI3K/Akt axis facilitates the metastasis of nasopharyngeal cancer [67].…”
Section: Tumor Invasion and Metastasismentioning
confidence: 99%
“…lncRNAs are non-coding RNA transcripts that exceed 200 nucleotides, and regulate gene expression at the epigenetic, transcriptional and post-transcriptional levels (55). Increasing evidence has demonstrated that aberrant lncRNA expression and dysfunctional lncRNA activity are associated with tumor initiation and progression (56)(57)(58)(59)(60)(61)(62)(63)(64). However, a full transcriptome analysis of the interactions between mRNAs and lncRNAs, and related regulatory networks in areca nut chewing induced TSCC have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA LNCAROD, which is up-regulated in HNSCC, is highly m 6 A modified by METTL3 and METTL14 in these samples. m 6 A modification stabilises LNCAROD, and LNCAROD expression correlates with poor prognosis and tumorigenicity in HNSCC [ 128 ]. In gastric cancer, m 6 A-associated genes were found to be dysregulated, and poor prognosis correlated with high expression of FTO and WTAP [ 129 ].…”
Section: Looking Ahead: Rna Modifications and The Ddr A Role For Rnamentioning
confidence: 99%